Strategi Membangun Brand Image Lembaga Pendidikan - M. Munir; Toha Ma'sum (Prodi Manajemen Pendidikan Islam STAI Darussalam, 2022)
Quality education is also a society's needs and expectations that educational institutions should respond positively to. Quality in the world of education is related to the efforts of an institution in providing satisfactory services for students. The amount of public interest and support for educational institutions must be considered and realized by the institution manager. Therefore, institutional managers are required to continuously improve their ability to compete. Brand image in this case is the image of an educational institution. A good image then an institution will get a positive value in the eyes of the community. Furthermore, from this positive view, the community will automatically think in the public's mind that the institution has good quality. The strategy to build a brand image in increasing the competitiveness of educational institutions is that educational institutions should always develop educational products that are already running well and add superior products that are not easily imitated by competitors because by adding superior products that are unique/not easily imitated by competitors will further enhance the competitiveness of educational institutions. In addition, it can maintain and improve the factors that form a brand image by improving the quality and quality of education so that they can be more competitive.